The Mediating Role of Self-Efficacy on Online Learning among Accounting Students - Muhammad, Kamaruzzaman; Ghani, Erlane K.; Johari, Razana Juhaida; Mohd Ali, Mazurina; Sukmadilaga, Citra (International Review of Management and Marketing, 2024)
This study examines the mediating role of self-efficacy in the effective online learning of accounting students. Specifically, this study examines whether self-efficacy can mediate the influence of student attitude towards online learning and course suitability for online learning in universities. This study uses a questionnaire distributed to students from public and private universities. Six hundred and sixty-two responses were received. Using mediation analysis, this study shows that self-efficacy serves as a mediator for the relationship between attitudes towards online learning and online learning. This study shows a significant direct influence between attitudes towards online learning and online learning. The results of this study indicate that the correlation between the appropriateness of the course and online learning is similar and has a statistically significant direct influence. This study also shows that self-efficacy partially complements the mediation of the correlation. The findings in this study provide additional insight into the various factors that can impact the effectiveness of online learning environments. These findings can assist universities in formulating strategies to optimise the content, activities, and assessments within such environments, thereby increasing their overall effectiveness. Furthermore, this study contributes to the existing literature by examining self-efficacy as a mediating role in an online learning environment in Malaysian universities.